Interaction of daytime and nighttime light exposure on objective sleep quality in patients with bipolar disorder: a cross-sectional analysis of the APPLE cohort - Yuichi Esaki; Kenji Obayashi; Keigo Saeki; Kiyoshi Fujita; Nakao Iwata; Jamie M. Zeitzer; Tsuyoshi Kitajima (Translational Psychiatry)
Abstract Light plays a crucial role in regulating nocturnal sleep patterns. This cross-sectional study evaluated the potential association between levels of light exposure in real-life settings and sleep parameters in individuals with bipolar disorder. We included 204 ambulatory individuals with bipolar disorder who participated in the APPLE (Association between Pathology of Bipolar Disorder and Light Exposure in Daily Life) cohort study. Daytime illuminance and sleep were assessed using actigraphy over a seven-day period. In addition, a portable light meter was used to evaluate the illuminance levels in the bedroom during nighttime. The median values of daytime illuminance and nighttime illuminance were 221.8 lux (interquartile range: 150.9–306.9 lux) and 2.3 lux (0.3–9.6 lux), respectively. Multivariable linear regression analyses, adjusting for potential confounders, revealed a significant association between greater daytime illuminance and higher sleep efficiency as well as shorter sleep onset latency and wake after sleep onset. Moreover, the interaction term of daytime and nighttime illuminance demonstrated a significant correlation with sleep efficiency (95% confidence interval [CI], −10.45 to −2.17; P = 0.003), sleep onset latency (95% CI, 0.18 to 0.91; P = 0.004), and wake after sleep onset (95% CI, 13.47 to 50.1; P < 0.001). Our findings indicate the existence of a significant positive correlation between daytime light exposure and sleep parameters in individuals with bipolar disorder. The interaction of increased daytime light and decreased nighttime light appears to be positively associated with sleep quality.